Rectangular Patch Antenna with Notch and Slot on Ground Plate for WLAN Application - Ramli, Mohamad Hafize; Abd Aziz, Mohamad Zoinol Abidin; Othman, Mohd Azlishah; Azizul Azlan, Siti Nurfarhanah; Hassan, Nornikman; Noor Azizi, Muhammad Syafiq; Dahalan, Abdul Halim (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
A new design of rectangular patch antenna was presented in this paper. This antenna was proposed to achieve wider bandwidth and good performance in return loss (S11), that is below -10dB. The design of this antenna was an improvement from the conventional rectangular patch antenna by making a parallel slot, rectangular slot on the ground plane and introducing a notch (dual mode). The rectangular antenna was designed and simulated using CST Microwave Studio. The application of this antenna was for WLAN application at 5.25 GHz. There was a slightly different result on the bandwidth and return loss value for the simulation and measurement.